Applying personality-informed treatment strategies to clinical practice : a theoretical and practical guide - Nevins, Bradley G. (New York, NY : Routledge, 2021)
"A comprehensive guide to assessing and addressing maladaptive personality traits, this text assists readers in factoring personality functioning into one's understanding and treatment of disorders. Dr. Nevins presents his Personality Wheel as a framework for therapeutically addressing the problematic personality patterns, styles, or traits related to most client's presenting problems and for determining the most effective manner by which to direct healthy personality change. Incorporating research, case studies, and worksheets, chapters provide a methodology for being more therapeutically effective in dealing with a client's unique personality styles and for assisting in the process of resolving the internal conflicts that negatively impact daily functioning. Clinical psychologists across all mental health fields, as well as those studying clinical psychology, will be able to better understand how personality informs pathology through the book's key insights into the primary driving forces underlying most mental health problems"--
The Importance of Personality -- The Science, Theory, and Therapeutic Principles of the Personality-Informed Treatment Perspective -- Personality : Processes and Functioning -- Interpersonal and Intrapersonal Relationship Processes -- Personality-Informed (PI) Therapy Personality Wheel -- Self-Regulation and Complex Change -- Personality Trait Regulation -- Personality Self State Regulation -- Treatment Guide for Personality-Informed Complex Assessment and Treatment -- Personality-Informed Phase-Oriented Treatment Planning Guide -- The Client-Therapist Relationship Process -- Personality Trait Regulation Guide : Format and Rationale -- Personality Trait Regulation Guide : Quadrant I -- Personality Trait Regulation Guide : Quadrant II -- Personality Trait Regulation Guide : Quadrant III -- Personality Trait Regulation Guide : Quadrant IV -- Conclusion and Future Directions.
OCLC-licensed vendor bibliographic record.
Keywords: Mental illness -- Treatment; Personality; PSYCHOLOGY / Mental Health